Benefits of physical exercise through multivariate analysis in sedentary adults and elderly: An analysis of physical fitness, health and anthropometrics - Guilherme da Silva Rodrigues; Andressa Crystine da Silva Sobrinho; Gabriel Peinado Costa; Leonardo Santos Lopes da Silva; João Gabriel Ribeiro de Lima; Leonardo da Silva Gonçalves; Larissa Chacon Finzeto; Carlos Roberto Bueno Júnior (Experimental Gerontology)
This study employed multivariate analysis to investigate the effects of a 14-week multicomponent training program on sedentary adults and older populations, focusing on improvements in physical fitness, health markers, and anthropometric measures. The data included 376 participants aged 30 to 84 years who had been inactive for at least 3 months. Results showed that participants aged 71 and above had lower systolic blood pressure, height, body mass, elbow flexion and extension, sitting and standing up from a chair, agility, 6-Minute Walk Test (6MWT), and handgrip strength values compared to younger age groups (p < 0.05). Initially, the 6MWT was inversely correlated with anthropometric measures and positively correlated with strength tests, but after the intervention, it remained correlated only with handgrip strength and agility. Interestingly, the elbow flexion and extension strongly correlated with other fitness measures pre-intervention, but these relationships weakened afterward. Agility became a key intermediary variable in the analysis. Despite improvements, anthropometric variables like body mass and waist circumference continued to have a strong relationship with fitness outcomes. Significant gains were observed in the 6MWT and elbow flexion and extension (p < 0.05), indicating improvements in aerobic fitness and strength. Multivariate analysis showed that hip circumference, chair stand test, handgrip strength, and agility significantly influenced 6MWT performance. Using multivariate analysis, we were able to highlight the importance of incorporating regular exercise into daily life to promote active and healthy aging. Furthermore, agility emerged as the most significant intermediate variable after the intervention. This insight suggests that improvements in agility may be crucial for physical fitness and overall health.